Ultrahigh specificity in a network of computationally designed protein-interaction pairs - Ravit Netzer (Nature Portfolio, 2018)
The molecular basis of ultrahigh specificity in protein-protein interactions remains obscure. The authors present a computational method to design atomically accurate new pairs exhibiting >100,000-fold specificity switches, generating a large and complex interaction network.